2004
DOI: 10.1021/ja038907v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Isotope Effects and Mechanism of Aqueous Ozone and Peroxone Decompositions

Abstract: Mechanism of ozone decomposition in aqueous solutions Reaction Rate constants in M, s units Ref.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 66 publications
3
58
0
Order By: Relevance
“…[4] These results conclude that the electron-transfer reaction [Eq. (3)] cannot be the rate-determining step, and a hydride transfer reaction [Eq.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[4] These results conclude that the electron-transfer reaction [Eq. (3)] cannot be the rate-determining step, and a hydride transfer reaction [Eq.…”
mentioning
confidence: 83%
“…(11)] has been made responsible [4] for the well-established AOP properties of the peroxone process and has been termed a "capped COH radical". [5] However, it is difficult to see how a species that has no free-radical character and only a very low intrinsic lifetime (see below) should have properties similar to that of COH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] In environmental chemistry, the hydroperoxyl radical is a highly oxidant molecule that reacts by addition to double bonds or by abstracting hydrogen atoms, and it is associated with peroxone chemistry and as a radical in advanced oxidation processes. [15][16][17][18] In the literature, a large amount of research work has been devoted to identify hydrogen-bonded complexes between HO 2 and neutral molecules. The interest in these complexes lies in the high stability of some hydrogen bonds formed by HO 2 (in particular, HO 2 has been shown to be a better proton donor than water).…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Goddard [31] have proposed that the reaction proceeds via a planar seven-membered-ring biradical intermediate (with the spin multiplicity of the triplet and singlet states being almost degenerate) to yield HOOOH and 3 O 2 ( Figure 3 and Table 1, entry 5). More recently, to explain hydrogen isotope effects on the reaction kinetics of the peroxone reaction in water, Lesko et al [32] have concluded that HO 3 À , the conjugate base of H 2 O 3 , may be generated from a reaction between the anion of hydrogen peroxide and O 3 ( Table 1, entry 6).…”
mentioning
confidence: 99%